A Measure of Consumer Complaining Behaviour in Service Industry: Scale Validation. Issue 1 (June 2015) - Kaur, Prabhjot; Sharma, Sanjeev Kumar
Consumer complaints are reflection of mistakes committed by the service provider. These help to show a mirror to the organization indicating the reality of the situation, which can be used to handle displeased customers. Service providers these days are focusing on providing easy and varied ways, through which people can represent their problems. It is imperative to keep hold of existing customers, considering the cost of acquiring new customers and competitiveness in the market. This study aims to check the reliability and validity of the construct of consumer complaining behaviour (CCB), from the perspective of the Indian service industry, especially banking, telecom and insurance. A total of eight factors, namely, redress-seeking complaint, friendly complaint, opportunism, third-party complaint, word-of-mouth complaint, switching, loyalty complaint and neglect, have been taken to develop scales in order to collect data from 180 customers by using the critical incident technique (CIT). Various tools of reliability and validity were applied on the collected data. Results revealed an adequate fit of the theoretical model proposed, by satisfying all the criteria of reliability and validity (content, convergent and discriminant). This construct can be used by marketers and researchers to understand various consumer dissatisfaction responses given in different industries. This paper is first of its kind, which has taken all the factors together and validated the construct in the Indian context.